Emergence agitation: current knowledge and unresolved questions - Lee, Seok-Jin (Korean J Anesthesiol, 2020)
Emergence agitation (EA), also referred to as emergence delirium, can have clinically significant consequences. The mechanism of EA remains unclear. The proposed risk factors of EA include age, male sex, type of surgery, emergency operation, use of inhalational anesthetics with low blood–gas partition coefficients, long duration of surgery, anticholinergics, premedication with benzodiazepines, voiding urgency, postoperative pain, and the presence of invasive devices. If preoperative or intraoperative objective monitoring could predict the occurrence of agitation during emergence, this would help to reduce its adverse consequences. Several tools are available for assessing EA. However, there are no standardized clinical research practice guidelines and its incidence varies considerably with the assessment tool or definition used. Total intravenous anesthesia, propofol, μ-opioid agonists, N-methyl-D-aspartate receptor antagonists, nefopam, α(2)-adrenoreceptor agonists, regional analgesia, multimodal analgesia, parent-present induction, and preoperative education for surgery may help in preventing of EA. However, it is difficult to identify patients at high risk and apply preventive measures in various clinical situations.The risk factors and outcomes of preventive strategies vary with the methodologies of studies and patients assessed.This review discusses important outcomes of research on EA and directions for future research.